2020
DOI: 10.1111/tran.12382
|View full text |Cite
|
Sign up to set email alerts
|

Making and unmaking political subjectivities: Climate justice, activism, and care

Abstract: Much recent work on climate justice and activism focuses on the broader sociopolitical economic contexts in which contestation occurs. These contestatory spaces in neoliberalised economies are frequently depoliticised through a variety of processes, strategies, practices, and actors. Recently this has been framed as the post-politicalwhereby dissent is legitimised as "democratic" only when it does not challenge the status quo of business-as-usual. Most of the analysis and commentary on the post-political has f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…For example, previous studies revealed the importance of individuals' emotions (anger, hate, and contempt), self-corrections ( Van den Bos, 2018;Feddes et al, 2020), and quest for significance (Kruglanski et al, 2014). We also propose that sense of urgency could be crucial, because when individuals feel there is no time left this may increase their perceived need for radical actions (Bond et al, 2020). In addition, our model could be tested in other contexts, such as in non-Western samples and societies (see Henrich et al, 2010a,b).…”
Section: Summary Considerations and Future Directionsmentioning
confidence: 73%
See 2 more Smart Citations
“…For example, previous studies revealed the importance of individuals' emotions (anger, hate, and contempt), self-corrections ( Van den Bos, 2018;Feddes et al, 2020), and quest for significance (Kruglanski et al, 2014). We also propose that sense of urgency could be crucial, because when individuals feel there is no time left this may increase their perceived need for radical actions (Bond et al, 2020). In addition, our model could be tested in other contexts, such as in non-Western samples and societies (see Henrich et al, 2010a,b).…”
Section: Summary Considerations and Future Directionsmentioning
confidence: 73%
“…The idea that people and groups least responsible for climate issues suffer the most severe consequences, despite not being responsible for causing for climate issues, is an important driving force for climate protesters (Han and Ahn, 2020). As such, protesters notice relative deprivation between social groups (the disproportionate burden of environmental hazards placed on less privileged people in terms of socio-economic status, Rainey and Johnson, 2009) and continents (the global South will be first to suffer the burden of climate change, Bond et al, 2020;Piispa and Kiilakoski, 2021). Therefore, social injustices and intercontinental injustices shape protesters' judgments of unfairness.…”
Section: The Spatial Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach therefore resists the foreclosure of the persistent political disagreement around this issue and challenges the “post‐political” framing that attempts to place climate change beyond political dispute and delegitimizes the expression of dissent. The “post‐political” framing only tolerates dissent as “democratic” when it does not challenge the status quo (Bond et al, 2020). The aim of democratic institutions, according to the radical democratic approach, is not to suppress conflict, but rather to facilitate its respectful expression, and in this way can defuse the potential that it is expressed violently (Mouffe, 1997, p. 27).…”
Section: The Radical Democratic Imaginarymentioning
confidence: 99%
“…We conclude our intervention by noting that blaming others for the disease's emergence and diffusion does nothing to address the immediate challenge of how to live with it, as New Zealand Prime Minister Jacinda Ardern has been quick to point out (Cousins, 2020; Friedman, 2020). Ardern has championed something close to a feminist geopolitical perspective (Bond, Thomas, & Diprose, 2020), which is attentive to how the discourses and practices of public health need to be attentive to the alarmist, uncaring and provocative geopolitical narratives of populist leaders. She and others, such as the Scottish leader Nicola Sturgeon, have urged citizens to exercise an ethic of “care and solidarity for one another” (GovScot, 2020) which acknowledges that human bodies, animals, including pets, and the virus share the same spaces.…”
Section: Introductionmentioning
confidence: 99%